Russian centre on the map of the martial arts tourism - Congress and festival in Saint Petersburg, Russia - Wojciech Cynarski (Universidad de León, 2018)
This report informs on the VIII International Congress "Sport, People and Health", held in Saint Petersburg between October 12 and 14, 2017, from the perspective of scientific tourism and martial arts tourism. We used qualitative methods (single-case study and participant observation) in doing the report, including descriptive, interpretative and evaluative contents. The congress gathered more than 600 participants. Martial arts and combat sports were a key content, with a total of 33 works presented on the topic, and also it was possible to attend martial arts and combat sports demonstrations. We conclude that this event was a good example of scientific and martial arts tourism and of the increasing willingness of Russian academics to participate in the international community of martial arts and combat sports researchers. Some suggestions for increasing the scientific impact of the event are provided.